Photoacclimation Responses in Subarctic Atlantic Phytoplankton Following a Natural Mixing-Restratification Event - Graff, Jason R.; Behrenfeld, Michael J. (Frontiers in Marine Science, 2018)
Strong physical disturbances in the surface ocean vertically redistribute plankton and lead to new relationships between organisms and their growth environment. Entrainment of phytoplankton to deeper depths decreases light exposure while stratification exposes cells in the surface mixing layer to higher light. Phytoplankton can rapidly respond to alterations in growth irradiance using photoacclimation processes such as nonphotochemical quenching and alterations in pigments and other macromolecules. While it is common to observe photophysiological responses to shifts in growth irradiance in the laboratory it is rare that a study is able to document these processes in the field in a lagrangian framework. We were able to follow a natural phytoplankton community for four days and observe rapid photophysiological responses and net accumulation patterns of biomass down to 200 m following a deep mixing and restratification event in the subarctic Atlantic ocean. Applying flow cytometry and fast rate repetition fluorometry (FRRf) we report on the photoacclimation responses of multiple taxonomic groups in relation to the rapidly evolving physical environment. Significant stratification occurred following the deep entrainment event, isolating cells within an actively mixing and shoaling surface layer, the lower euphotic zone, and below the photic zone. Distinct differences in patterns of accumulation and photoacclimation are apparent between these depths of disparate light histories. Photoacclimation patterns are generally consistent between Synechococcus, picoeukaryote, and nanoeukaryote groups yet diel patterns and variability in the range of photoacclimation suggest divergent physiology. Results from continuous FRRf measurements collected on bulk seawater show a decrease in the number photosystem II reaction centers and a concurrent increase in the functional cross section with implications for maintaining photosynthetic rates throughout the mixed layer. Understanding group specific differences as well as bulk community acclimation strategies will be important for informing models relying on photoacclimation parameters to determine growth and accumulation rates and net primary production. More so, the rates at which cells acclimate within the context of the frequency and spatial dynamics of storm events, such as the one recorded here, directly impact interpretations and applications of remote retrievals of phytoplankton chlorophyll, carbon, and their ratio in the context of unbalanced growth.